User Engagement and Satisfaction: The Case of Web Digital Library - Noorman Masrek, Mohamad; Hudzari Razali, Mohammad; Ramli, Ishak; Andromeda, Trias (International Journal of Engineering and Technology, 2018)
In the era of Internet, user engagement has become more significant and relevant due to the intensification of interaction between the user and web applications. Today, most of the computer-based information systems that are in use to support our day-to-day activities are deployed on the web-based platform. The quality and intensity of interaction between the user and these web-based applications are referred as user engagement. While studies on user engagement have been quite extensively reported in the literature, very few have attempted to examine its relationship with user satisfaction. To this effect, this study was conducted with the aim of filling this research gap. The study used survey as the research methodology and the web, digital library as the object of assessment. 299 respondents provided the research data that were analyzed using Partial Least Square Structural Equation Modeling (PLS-SEM) approach. The results of the study showed that user engagement is a strong predictor of user satisfaction. The findings provide additional empirical evidence on the topic of user engagement.Â Â